(untitled) (Research, Society and Development, 2020)
Every organization is made up of people and the full exercise of their activities can be conditioned to the motivational aspects of these individuals in the work environment. In this sense, the present research, based on the motivational theoretical approach of people management, according to Herzberg’s two factors, aims to identify the factors that influence the motivation of Emater employees - Regional Caiapó, located in the West region of Goiás, carrying out a study case. The methodology used was the descriptive research, aiming at the identification and analysis of the data, with the application of a questionnaire that evidences the factors of satisfaction and dissatisfaction of the collaborators. The results obtained showed satisfaction with the work itself and its contribution to the completion of a task. Dissatisfaction referred to salary issues and possibilities for professional growth and development.